1997
DOI: 10.1152/ajpregu.1997.273.3.r1067
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin gene expression is suppressed after lipopolysaccharide or interleukin-1 beta injections in rats

Abstract: Proinflammatory cytokines play an important role in the pathogenesis of anemia in inflammatory diseases. Interleukin-1 (IL-1) and tumor necrosis factor-alpha (TNF-alpha) have been reported to inhibit the synthesis of erythropoietin (EPO) in vitro. To evaluate the in vivo significance of this observation, we have investigated effects of the administration of bacterial lipopolysaccharide (LPS) and IL-1 beta on renal EPO production in rats. Measurements by competitive reverse-transcription polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 0 publications
6
51
0
1
Order By: Relevance
“…Consistent with reduced EPO production in LPStreated rats [30], the present study found downregulation of EPO gene and protein expression following LPS treatment in A549 cells. Potential mechanisms include inhibition of EPO gene expression by the transcription factor nuclear factor (NF)-kB [31], which is upregulated by LPS, or a secondary effect through induction of pro-inflammatory cytokines including interleukin-1b and tumour necrosis factor-a, which have also been shown to inhibit EPO gene and protein expression [32].…”
Section: Expression Of Epo and Epor Has Been Demonstrated In A Widesupporting
confidence: 87%
“…Consistent with reduced EPO production in LPStreated rats [30], the present study found downregulation of EPO gene and protein expression following LPS treatment in A549 cells. Potential mechanisms include inhibition of EPO gene expression by the transcription factor nuclear factor (NF)-kB [31], which is upregulated by LPS, or a secondary effect through induction of pro-inflammatory cytokines including interleukin-1b and tumour necrosis factor-a, which have also been shown to inhibit EPO gene and protein expression [32].…”
Section: Expression Of Epo and Epor Has Been Demonstrated In A Widesupporting
confidence: 87%
“…Inflammatory cytokines, such as TNFa, have been shown to repress hypoxia-responsive Epo-producing ability, 30,31 and are assumed to be key pathogenic regulators of anemia of chronic disease 32 and UUO-induced renal fibrosis. 18,19,33 In turn, TGFb/Smad signaling is the central pathway for myofibroblast activation and transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the in vivo studies performed till today focused mainly on the inhibitory effects of these cytokines on kidney EPO expression under hypoxic conditions. 34,35 The analysis of two models characterized by 36 The regulation of EPO gene expression during hypoxia has been widely explained, 37 but several points concerning the tissue-specific EPO gene expression and the after-birth switch between the fetal hepatic production and the adult kidney counterpart still need further clarifications. The HIF transcription factor family has been initially identified as the Figure 14 Mouse hepatocytes stimulation with IL-6 in normoxic conditions.…”
Section: Discussionmentioning
confidence: 99%